Responses of the Housefly, Musca domestica, to the Hytrosavirus Replication: Impacts on Host's Vitellogenesis and Immunity - Kariithi, Henry M.; Yao, Xu; Yu, Fahong; Teal, Peter E.; Verhoeven, Chelsea P.; Boucias, Drion G. (Frontiers in Microbiology, 2017)
Abstract Hytrosaviridae family members replicate in the salivary glands (SGs) of their adult dipteran hosts and are transmitted to uninfected hosts via saliva during feeding. Despite inducing similar gross symptoms (SG hypertrophy; SGH), hytrosaviruses (SGHVs) have distinct pathobiologies, including sex-ratio distortions in tsetse flies and refusal of infected housefly females to copulate. Via unknown mechanism(s), SGHV replication in other tissues results in reduced fecundity in tsetse flies and total shutdown of vitellogenesis and sterility in housefly females. We hypothesized that vitellogenesis shutdown was caused by virus-induced modulation of hormonal titers. Here, we used RNA-Seq to investigate virus-induced modulation of host genes/pathways in healthy and virus-infected houseflies, and we validated expression of modulated genes (n=23) by RT-qPCR. We also evaluated the levels and activities of hemolymph AMPs, levels of endogenous sesquiterpenoids, and impacts of exogenous hormones on ovarian development in viremic females. Of the 973 housefly unigenes that were significantly modulated (padj ≤0.01, log2FC ≤−2.0 or ≥2.0), 446 and 527 genes were downregulated and upregulated, respectively. While the most downregulated genes were related to reproduction (embryogenesis/oogenesis), the repertoire of upregulated genes was overrepresented by genes related to non-self recognition, ubiquitin-protease system, cytoskeletal traffic, cellular proliferation, development and movement, and snRNA processing. Overall, the virus, Musca domestica salivary gland hytrosavirus (MdSGHV), induced the upregulation of various components of the siRNA, innate antimicrobial immune, and autophagy pathways. We show that MdSGHV undergo limited morphogenesis in the corpora allata/corpora cardiaca (CA/CC) complex of M. domestica. MdSGHV replication in CA/CC potentially explains the significant reduction of hemolymph sesquiterpenoids levels, the refusal to mate, and the complete shutdown of egg development in viremic females. Notably, hormonal rescue of vitellogenesis did not result in egg production. The mechanism underlying MdSGHV-induced sterility has yet to be resolved.